Phytochemical profile and biological activities of 'Ora-pro-nobis' leaves (Pereskia aculeata Miller), an underexploited superfood from the Brazilian Atlantic Forest - Garcia, Jéssica A.A. (2021)
South to Northeast of Brazil, ora-pro-nobis leaves are used in traditional cuisine, featuring as an ingredient of various sweet and savoury dishes. In some low-income communities, it is known as the ‘meat of the poor’, being the main protein source available.1 The aim of the present work was to perform an inedited study on the phytochemical profile and some biological activities of P. aculeate leaves, with the view of expanding the current knowledge on the potentialities of this superfood. For this purpose, its hydroethanolic extract was characterized in terms of phenolic composition, antioxidant, and antibacterial capabilities and finally the hepatotoxicity of the extract was evaluated. A total of ten phenolic compounds were identified via high-performance liquid chromatography coupled to diode array detector and mass spectrometer (HPLC–DAD–ESI/MSn): two phenolic acids (caffeic acid derivatives) and eight flavonoids (quercetin, kaempferol and isorhamnetin glycoside derivatives). Caftaric acid was the extract’s major phenolic constituent, accounting for more than 49% of the phenolic content, followed by quercetin-3-O-rutinoside (14.99%) and isorhamnetin-O-pentoside-O-rutinoside (9.56%). The total phenolic content found in the hydromethanolic extract was relevant (23.75 mg/g). A broad study of the extracts’ antioxidant activity was carried out, using a set of five distinct methods: two cell-based methods (1) oxidative haemolysis inhibition assay (OxHLIA); (2) the inhibition of the production of thiobarbituric acid reactive substances (TBARS); besides three chemical in vitro assays (3) reduction of the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH); (4) reduction of the 2,2-azino-bis (3-ethylbenzothiazoline-6-sulphonate) cation (ABTS) and (5) hydroxyl radical scavenging assay.2 Overall, the ora-pro-nobis leaf extract showed relevant values of antioxidant activity, even higher than Trolox in the DPPH and ABTS trials. The antioxidant activity verified for the hydroethanolic leaf extract of P. aculeata is possibly related to its phenolic composition; the predominant constituents of the extract, i.e. caftaric acid and rutin, have widely proven antioxidant activities.1 Furthermore, the evaluated extract showed no toxicity against a non-tumour liver primary culture PLP2, at the highest tested concentration (400 μg/mL). The antimicrobial activity exhibited by the extract against both Gram-positive (Enterococcus faecalis, Listeria monocytogenes, MRSA – Methicillin-resistant Staphylococcus aureus) and Gram-negative (Escherichia coli, Klebsiella pneumoniae, Morganella morganii, Proteus mirabilis, and Pseudomonas aeruginosa) bacteria (MIC values between 5 to 20 mg/mL) suggests the presence of a broad spectrum of phytochemicals with antimicrobial activity. The extract was more active against K. pneumonia than the antibiotic ampicillin, whereas against M. morganii it presented equivalent inhibitory effect. Therefore, the information reported here not only corroborates the importance of the production and consumption of P. aculeata leaves by the low income population to improve nutrition, but also reinforces their potential as a sustainable source of promising food ingredients to be used both for food enrichment and preservation.